Diseño y ejecución del plan de acción para la implementación de los dos primeros subsistemas del sistema de información y gestión del empleo público en la Contraloría General del Quindío (2014)
This work presents the design of an action plan for the implementation of the first two subsystems of the information system and management of public employment SIGEP, in the Comptroller General of Quindío. Through the implementation of the activities outlined in the action plan, this agency will be able to implement the "human resources subsystem" fully and completely develop modules institutions and organizational structure, which are part of the "institutional organization subsystem"; the remaining modules could not be developed due to the administrative act requirements of these modules, do not meet the standards set by the Administrative Department of the Public Function (DAFP). Additionally, there are some modules that are not yet enabled on the SIGEP. Finally, the results obtained in the process of implementing the action plan are presented; also conclusions and recommendations for the comptroller general of Quindío in order to continue with the implementation of the action plan.